GAMBARAN INDEKS ERITROSIT PADA PENDERITA TUBERKULOSIS PARU DENGAN RIWAYAT DIABETES MELITUS DI PUSKESMAS KOTA JAMBI - Mustopa, RD.; Lestari, Wuni Sri; Pradasari, Nur Meisy (NHM PRESS, 2024)
Pulmonary tuberculosis ranks second after India, with the number of sufferers reaching 969,000 people. According to the Central Bureau of Statistics (BPS), the number of pulmonary TB cases in Jambi Province is 12,682 people. In 2022, across 11 districts, there were 1,942 cases reported in Jambi City (BPS, 2022). The risk of pulmonary TB can increase in patients with diabetes mellitus (DM). This study aims to describe the erythrocyte index in pulmonary TB patients with a history of DM at public health centers in Jambi City. The research method used is descriptive with a cross-sectional approach, including variables such as gender, age, and duration of treatment. This study was conducted from April to May 2024, with a sample of 30 pulmonary TB patients with a history of DM from several health centers in Jambi City. From the study conducted on pulmonary TB patients with a history of DM based on gender, the erythrocyte index showed 24% microcytic hypochromic in males and 23% in females. Based on age, the erythrocyte index for those aged 20-55 years was 24%, while for those aged 56-75 years, it was 23%. Based on the duration of treatment, the erythrocyte index was 25% for treatment duration ≤ 2 months and 22% for > 2 months.